Analysis of the radial and ulnar arteries using ultrasound and a vascular visualization device in children. Issue 6 (28th March 2022) - Kemmochi, Makoto; Nawa, Yuko; Ohno, Sho; Sawashita, Yasuaki; Terada, Hirofumi; Oba, Koji
Abstract: Background: Radial artery is the preferred site for cannulation. Recently, the ulnar artery was chosen as an alternative in adults. Aims: We aimed to measure the diameter and depth of the ulnar and radial arteries using ultrasound, and our secondary purpose was to evaluate their anatomical position using a near‐infrared transcutaneous illumination device. Methods: Forty‐eight children (age range: 0–144 months) were assigned to the following groups: group Infant (aged <12 months), group Preschool (aged ≤12 to <72 months), and group School (aged ≥72 months). The diameter, depth, and position of the ulnar and radial arteries were compared between groups. Results: There was no significant difference between the diameters of the ulnar and radial arteries. In group Infant, group Preschool, and group School, mean diameters of the ulnar artery were 1.27 ± 0.15 mm, 1.62 ± 0.27 mm, and 2.03 ± 0.28 mm, respectively, and the radial artery were 1.29 ± 0.15 mm, 1.69 ± 0.27 mm, and 2.06 ± 0.29 mm, respectively. The corresponding differences between the diameters of ulnar and radial arteries were −0.02 mm, −0.07 mm, and −0.02 mm [95% CI −0.16 mm to 0.12 mm, −0.25 mm to 0.11 mm, and −0.25 mm to 0.21 mm; p  = .776, p  = .411, and p  = .852]. In groups Preschool and School, the ulnar artery was at the recommended depth of 2–4 mm for arterial cannulation compared with the radial artery. In the Infant, Preschool, and School age groups, the ulnar and radial arteries were at the recommended depth of 2–4 mm for arterial cannulation in 70.0%, 100.0%, 93.8%, and 80.0%, 65.0%, and 50.0% of the cases, respectively. (difference: −10.0%, 35.0%, and 43.8%, 95%; CI −43.4% to 23.4%, 14.1% to 55.9%, and 19.4% to 68.1%, respectively). Conclusions: The ulnar artery can be considered a promising alternative to the radial artery for facilitating arterial cannulation in children.